De Homokrant : voor vrouwen en mannen (Antwerpen: FWH)
"Fonds Suzan Daniel (FSD)Periodiciteit : maandelijksRedactie : Atletiekplein 4, 9000 Gent ; vanaf 10(1984) 6 : Dambruggestraat 204, 2000 Antwerpen"